The Origins of Economic Environment and its Consequences - R. M. Nureev (Мир новой экономики)
During the First World War, nationalization of the economy of the belligerent countries takes place. The war was extremely long and devastating. This was a surprise for all belligerent countries. The fact is that the experience of past wars (Franco-Prussian, Balkan) made me expect the opposite. However, the high level of military equipment achieved did not allow us to receive rapid military successes on the fronts of the First World War. To mobilize resources, the governments of the belligerent countries were forced to abandon the market methods of regulating the economy in favor of the command. In Germany and Great Britain, this process covered both industries and agriculture. This experience meant the beginning of the transition from a purely market economy to a mixed one and proved extremely tempting for the Bolsheviks in the construction of a new economy in Soviet Russia. The practice of “military communism” showed the extraordinary possibilities of administrative-command methods of government. During the period of forced industrialization and complete collectivization, an administrative-command system is being formed.